Identification of factors required for m6A mRNA methylation in Arabidopsis reveals a role for the conserved E3 ubiquitin ligase HAKAI - Růžička, Kamil; Zhang, Mi; Campilho, Ana; Bodi, Zsuzsanna; Kashif, Muhammad; Saleh, Mária; Eeckhout, Dominique; El-Showk, Sedeer; Li, Hongying; Zhong, Silin; Jaeger, Geert De; Mongan, Nigel P.; et al. (Wiley, 2017)
N6-adenosine methylation (m6A) of mRNA is an essential process in most eukaryotes, but its role and the status of factors accompanying this modification are still poorly understood.